New findings to discussion on local versus fluctuating stocks of pink salmon Oncorhynchus gorbuscha - Alexander M. Kaev; Lev A. Zhivotovsky (Известия ТИНРО, 2016)
Some patterns in dynamics of catch and biological parameters of pink salmon Oncorhynchus gorbuscha returned to the southeastern coast of Sakhalin Island and the Aniva Bay in 2014 (additional peak in the return abundance and unusual increase in relative fecundity of females in the second half of the return) could be interpreted as presence of the fish from Kuril Islands. This hypothesis was proven by the scale structure analysis, using the known difference between the pink salmon from southern Sakhalin and Iturup Island by the total number of sclerites and the depth of the local minimum in the first eight intersclerite distances caused by different environments. The fish of Kuril origin was found in all samples collected on the southeastern coast of Sakhalin on August 6, 7, 14, and 18, with its portion increasing in later catches, and in the sample collected in the Ostrovka River on the eastern shore of the Aniva Bay on August 18, but wasn’t found in the sample collected in the same site on August 25, and only a small portion of the fish of Kuril origin was found in the marine sample taken at the Busse Lagoon. The pink salmon in the Kura River on the western shore of the Aniva Bay had mixed origin, too, but without signs of the Kuril origin. This is the first real evidence of the salmon straying and the hypothesis of fluctuating stocks of pink salmon obtained with the ichthyological methods, though possibility of the straying is debating many years. This phenomenon has high theoretical and practical importance. The new findings show that mass movement of pink salmon between different reproduction regions is quite real, though maybe it happens rarely, presumably during the shift of domination between the odd- and even-year broodlines. The straying of low intensity may be invisible with routine methods, that’s why thorough monitoring of pink salmon stocks in different areas of its reproduction is necessary for understanding its population structure and dynamics, including detailed environmental, ichthyological and genetic studies.